Pengaruh Deviden, Ukuran Perusahaan dan Volatilitas Laba terhadap Volatilitas Saham Otomotif - Mutiara Lusiana Annisa; Ruth Samantha Hamzah (P3M Politeknik Negeri Bengkalis, 2025)
This research investigates the effect of dividend policy, firm size, and earnings volatility on stock price volatility in automotive and vehicle component companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Stock price volatility is a key factor for investors, as it represents the degree of investment risk in the capital market. The study applies panel data regression analysis using the Random Effect Model (REM), determined through the Chow test, Hausman test, and Lagrange Multiplier (LM) test. The sample includes seven companies selected according to specific criteria within the automotive and vehicle components sector. Dividend policy, firm size, and earnings volatility are used as independent variables, while stock price volatility serves as the dependent variable. The results reveal that dividend policy does not significantly impact stock price volatility. Firm size, on the other hand, has a positive but marginally significant influence on stock price volatility. Earnings volatility shows no significant effect. These findings align with the signaling theory, which posits that financial information provided by companies, such as firm size and earnings stability, acts as a signal for investors when evaluating stock risks. This study offers practical implications for company management in optimizing financial strategies and provides useful insights for investors when considering company fundamentals in investment decisions.